Immune checkpoint blockade in melanoma - Buchbinder, Elizabeth (Henry Stewart Talks, 2017)
Checkpoint inhibition in melanoma, Immunotherapy in the adjuvant setting, Biomarkers of immune response, The future of immunotherapy in melanoma, Targeting release of cancer antigens, Targeting cancer antigen presentation, Targeting priming and activation of the immune system, Targeting trafficking and infiltration of T-cells, Targeting recognition and killing of cancer cells